Insights into Increasing the Implementation of Concrete Overlay Rehabilitation Methods for Highway Pavements. Issue 3 (March 2023) - Sheffield, Matthew T.; Cavalline, Tara L.; Dean, Greg
Concrete overlays provide a promising solution to extending pavement life, and are currently the focus of the Federal Highway Administration Every Day Counts initiative. Despite their potential benefits, concrete overlays are not commonly used in many areas of the U.S.A., including the Southeast. A survey of 19 paving contractors active in the Southeastern U.S.A. was performed to quantify recent concrete overlay projects performed by these contractors, to assess the capabilities of contractors to construct concrete overlays in this region, and to identify barriers to implementation of concrete overlays as well as opportunities to increase their use. Findings indicated contractors in the region either had extensive overlay experience or no experience constructing concrete overlays. Regardless of the experience level of the contractor, the primary barrier to implementation is that this type of work is not being let for bid. Concerns about traffic control and safety was the second most important barrier among all contractors. Experienced contractors indicated the lack of available and skilled construction personnel were also key barriers. Inexperienced contractors cited concerns about the length and duration of construction as the third most important barrier. Respondents indicated an eagerness to bid on and complete overlays. The results of this study provide insight to regional state highway agencies, municipalities, and design engineers of the capabilities of concrete pavement contractors in the region to complete concrete overlay projects. The findings will help agencies understand the capabilities and concerns of concrete paving contractors and aid in informed decisions about overlays.